2001
DOI: 10.1258/0022215011908603
|View full text |Cite
|
Sign up to set email alerts
|

Audiological findings in pregnancy

Abstract: This investigation was carried out in the Audiology and Speech Pathology Section of the Department of Otorhinolaryngology of Hacettepe University. The pregnant group comprised of 20 women followed by the Department of Gynaecology and Obstetrics of the same university; 18 non-pregnant women comprised the control group. The aim of this investigation was to study the relationship between hormonal changes in pregnancy and cochlear functions. All subjects underwent ENT examination, audiologic and acoustic immitance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 8 publications
3
56
0
8
Order By: Relevance
“…Furthermore, BAEPs were also examined to determine the differences in pregnant women between trimesters. Sennaroglu and Belgin [9] investigated the audiological findings in different trimesters of normal pregnancy and reported that BAEP results showed no significant differences among trimesters. They found low-frequency hearing loss and tolerance problems in pregnancy mimicking cochlear pathology from the first to the third trimester, which returned to normal in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, BAEPs were also examined to determine the differences in pregnant women between trimesters. Sennaroglu and Belgin [9] investigated the audiological findings in different trimesters of normal pregnancy and reported that BAEP results showed no significant differences among trimesters. They found low-frequency hearing loss and tolerance problems in pregnancy mimicking cochlear pathology from the first to the third trimester, which returned to normal in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…They found low-frequency hearing loss and tolerance problems in pregnancy mimicking cochlear pathology from the first to the third trimester, which returned to normal in the postpartum period. However, no consensus as yet exists regarding the effects of hormones on hearing function [7,9]. Bruce and Russell [10] reported the hormonal changes affecting neural conduction time and suggested that retention of water and sodium due to variation in levels of sex steroids during the menstrual cycle may influence the axonal conduction time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Quantifizierung der angegebenen Ohrgeräusche und eine BERA wurden von den Autoren jedoch nicht durchgeführt. Interessanterweise berichteten viele Studien, welche schwangerschaftsassozierte kochleovestibuläre-und fazialmotorische Störun-gen evaluierten, von einer regelmäßigen postpartalen Remission der Beschwerden und pathologischen Befunde, die in vielen Fällen ohne therapeutische Maß-nahmen erfolgten [4,6,7].…”
Section: Diskussionunclassified
“…Diskutiert werden multiple Ursachen: virale Infektionen, schwangerschaftsbedingte hormonale Veränderungen, Immunsuppression und Flüssigkeitsverschiebungen intra-und extrazellulärer Kompartimente. Eine Studie an einem Kollektiv unauffäl-liger Schwangerer konnte zudem aufzeigen, dass es zu -inapparenten -Verände-rungen der Hörleistung während der Gravidität kommt [4].…”
unclassified